2013
DOI: 10.7453/gahmj.2013.2.1.007
|View full text |Cite
|
Sign up to set email alerts
|

Homeopathic Medications as Clinical Alternatives for Symptomatic Care of Acute Otitis Media and Upper Respiratory Infections in Children

Abstract: The public health and individual risks of inappropriate antibiotic prescribing and conventional over-the-counter symptomatic drugs in pediatric treatment of acute otitis media (AOM) and upper respiratory infections (URIs) are significant. Clinical research suggests that over-the-counter homeopathic medicines offer pragmatic treatment alternatives to conventional drugs for symptom relief in children with uncomplicated AOM or URIs. Homeopathy is a controversial but demonstrably safe and effective 200-year-old wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 155 publications
(282 reference statements)
0
28
0
1
Order By: Relevance
“…6 Parents unintentionally use overdoses due to lack of symptom relief which is a subject of worry, especially with conventional medicines. 43 In case of homoeopathic medicines, a survey found that OTC use of homoeopathic medicines was most frequent for the treatment of respiratory problems, 44 and another study found no effect of self-selected treatment (by parents) beyond placebo for the prevention of URTI in children. 23 Homoeopathy as primary treatment: In a case series of URTI in children below 5 years of age illustrated that recurrent episodes of URTI decrease following 6 months of treatment with individualised homoeopathic medicines.…”
Section: Resultsmentioning
confidence: 99%
“…6 Parents unintentionally use overdoses due to lack of symptom relief which is a subject of worry, especially with conventional medicines. 43 In case of homoeopathic medicines, a survey found that OTC use of homoeopathic medicines was most frequent for the treatment of respiratory problems, 44 and another study found no effect of self-selected treatment (by parents) beyond placebo for the prevention of URTI in children. 23 Homoeopathy as primary treatment: In a case series of URTI in children below 5 years of age illustrated that recurrent episodes of URTI decrease following 6 months of treatment with individualised homoeopathic medicines.…”
Section: Resultsmentioning
confidence: 99%
“…8 Clinical trials have shown homeopathic treatment to be effective in preventing and treating upper respiratory tract infection in children, [9][10][11][12] and suggest that it may provide an alternative treatment option to conventional drugs for children with acute uncomplicated infections. 13 These studies also found that homeopathic treatment is associated with fewer adverse effects, is more cost-effective, and induces earlier symptom resolution compared with conventional medicines. 12,13 Individualized homeopathic treatment involves the use of a single remedy to treat the totality of the symptoms of a patient, 14 whereas a complex is the combination of wellindicated remedies for a specific condition combined into one vehicle.…”
Section: Introductionmentioning
confidence: 94%
“…13 These studies also found that homeopathic treatment is associated with fewer adverse effects, is more cost-effective, and induces earlier symptom resolution compared with conventional medicines. 12,13 Individualized homeopathic treatment involves the use of a single remedy to treat the totality of the symptoms of a patient, 14 whereas a complex is the combination of wellindicated remedies for a specific condition combined into one vehicle. 13,14 The homeopathic complex used in this study is commercially available in the South African market under the trade name TonzolytÒ and is marketed for the treatment of acute or chronic tonsillitis and pharyngitis.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations